PENGARUH MARKETING MIX, WORD OF MOUTH, DAN PERSONAL SELLING TERHADAP MINAT PEMBIAYAAN MIKRO NASABAH BSI KC SOEHAT MALANG - Dewi Nurhasana; Maslichah Maslichah; Afifudin Afifudin (Fakultas Ekonomi dan Bisnis Universitas Islam Malang, 2022)
The purpose of this study is to determine the influence of marketing mix, word of mouth, and personal sellingon the microfinance interests of BSI KC Soehat Malang customers. The method used is a cholerationalquantitative method with several stages of research which include the dissemination of questionnaires, datacollection, and analyzing data. The questionnaire was tested using validity test, reality test, normality test,multicholinearity test, heteroskedasticity test, multiple linear regression analysis, F test, Determination test(R2), and t test. The results of this study show that the variables of marketing mix and personal selling have apositive and significant effect on the microfinance interest of BSI KC Soehat Malang customers. Meanwhile, theword of mouth variable has a negative and significant effect on the interest of microfinancers of BSI KC SoehatMalang customers